Development of an Expert System to Select Materials for the Main Structure of a Transfer Crane Designed for Disabled People - Jamett-Dominguez, M; Urrea-Onate, E; Henriquez-Diaz, G (Elsevier Ltd, 2015)
This paper shows the development of an expert system for the selection of materials to be used in the construction of the main structure of a crane-like device for transporting persons with physical disabilities. The proposed method includes a stage in which the theory of the characteristics of the materials was used and another one that involves solely computational development with the application of fuzzy logic. For this, the fuzzy logic toolbox of Matlab® was used and both the data input and output of the solution were worked out on Simulink®. The data used were 32 alloys with features such as ultimate stress, yield stress, elongation, availability in the country (Chile), cost, ease of welding, hardness, fracture type, and corrosion (fresh water, water vapor or air). The end result gave a material that met 100% of the requirements, three met 90% and two only 75%. The most important conclusions are two: (1) the selection characteristics were based on the particular needs, but a great advantage of this system is that it can be used countless times in similar tasks or it can be modified only in those parts that need to be changed, also serving as a reference for creating other expert systems, and (2) it combines the use of an expert system with fuzzy logic, so that the overall system is enhanced. © 2014 Elsevier Ltd. All rights reserved.